KOMPARASI NILAI FAKTOR AMPLIFIKASI TANAH DENGAN PENDEKATAN SSA DAN HVSR PADA WILAYAH KECAMATAN TEMBALANG KOTA SEMARANG - Partono, Windu; Irsyam, Masyhur; R.W, Sri Prabandiyani; Maarif, Syamsul (TEKNIK, 2013)
Several methods for evaluating the effect of site specific condition of soil layers against earthquakes are presently available. Site Specific Analysis (SSA) and Horizontal-to-Vertical Spectral Ratio (HVSR) are two methods commonly used for estimating the amplification factor of soil layers above bedrock. SSA can be performed using subsurface shear wave velocities and dynamic soil properties (density, shear modulus and damping). The HVSR is a simple method for estimating the site amplification factor. Based on the time and budget requirement HVSR is more efficient and effective compare to SSA method.This paper presents result of SSA and HVSR methodscomparison for estimating the amplification factor of soil layers. Two boring locations and six single station seismometer tests were perform within Tembalang District Area.